Dolutegravir reported adverse drug reactions: a systematic review - Wadesango, Lesley (My University, 2022)
The first-line regimen for the management of Human Immunodeficiency Virus (HIV) has evolved over the years and until recently was Tenofovir (TDF)-Emtricitabine (FTC) and Efavirenz (EFV). However, the use of EFV has now been limited due to adverse neurosensory effects and a low genetic barrier to resistance. This EFV-based regimen has been replaced with a Dolutegravir (DTG)-based regimen due to its high genetic barrier to resistance. Studies have reported a higher risk of Immune Reconstitution Inflammatory Syndrome (IRIS), weight gain, insomnia, and neural tube defects amongst people who received DTG. This review aimed to assess the adverse drug reaction (ADR) profile of Dolutegravir by identifying and classifying Dolutegravirassociated adverse drug reactions. A search of the published literature for studies reporting ADRs to DTG was conducted usingspecified terms: Dolutegravir‘‘, Antiretroviral‘‘, ―Highly active antiretroviral‖, combination‘‘, regimen‘‘, Human Immunodeficiency Virus‘‘, Adverse effects‘‘, Acquired Immunodeficiency Syndrome‘‘, Adverse drug reactions‘‘, ―pharmacovigilance‖ and Adolescent‘‘. A review of all titles and abstracts to determine eligibility based on set criteria was conducted. An evaluation of the full texts of the articles was done and studies were assessed for their final eligibility for data extraction. After the selection of the final study sample, a data extraction form was used to extract data. Data was classified, categorized and summarized into tables. A narrative synthesis was done to describe and discuss the outcomes. Nausea and diarrhea were the most reported gastrointestinal (GI) ADRs. Headache, dizziness and fatigue were reported in most studies reporting on central nervous system ADRs. Insomnia was the most commonly reported neuropsychiatric ADR while rash featured highest amongst the dermatological ADRs. Of all the other ADRs recorded of particular interest is weight gain, high Alanine Transaminase (ALT) and Immune Reconstitution Inflammatory Syndrome (IRIS). The ADRs reported are similar to the reactions described in most of the package inserts. This study has demonstrated that the prevalence of ADRs can affect treatment continuity and thus cause treatment resistance. These findings can be employed by physicians to identify ADRs as early as possible to target and support earlier interventions for patients to be able to continue their treatment even after experiencing ADRs.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Pharmacy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022